Bangladesh : Joint Staff Assessment of the Interim Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report, 2003)
This paper presents a Joint Staff Assessment of the Interim Poverty Reduction Strategy Paper (I-PRSP) for Bangladesh. The I-PRSP lays out a broader vision for the future along with a medium-term economic strategy. The IMF staff considers that Bangladesh's I-PRSP constitutes a cohesive policy framework to increase growth and reduce poverty. However, some weaknesses remain to be addressed in the transition to the full PRSP. It will be important to more sharply prioritize near-term policies in key sectors and antipoverty programs, and incorporate their cost into the medium-term budget framework.